AI-Driven Leadership And Its Impact On Employee Performance In The Era Of Industry 5.0 - Anitiyo Soelistiyono; Istiyawati Rahayu; Imam Sucipto (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
The emergence of Industry 5.0 marks a paradigm shift in the relationship between humans and technology, emphasizing collaboration, personalization, and sustainability in organizational practices. Within this context, AI-driven leadership has gained attention as a transformative approach to guiding employees and enhancing performance outcomes. Recent studies since 2020 highlight that artificial intelligence not only supports decision-making and data-driven strategies but also reshapes leadership styles by fostering agility, adaptability, and employee engagement. This literature review examines the intersection of AI-driven leadership and employee performance, with a particular focus on how AI tools influence motivation, productivity, and job satisfaction. Evidence suggests that leaders who effectively integrate AI technologies into their leadership practices can create more personalized work environments, encourage innovation, and improve decision-making processes. However, concerns regarding ethics, employee trust, and technology overdependence remain significant challenges. By synthesizing recent research, this study contributes to a deeper understanding of how AI-driven leadership can be harnessed to optimize employee performance in the evolving Industry 5.0 landscape.